PKM Upaya Peningkatan Pemahaman Guru-Guru Akuntansi Sekolah Menengah Kejuruan Terhadap Materi Akuntansi Desa - Vita Fitria Sari; Dewi Febriyani; Mayar Afriyenti (Universitas Negeri Padang, 2019)
Since the issuance of the 2013 revised curriculum in 2018 it has become a challenge for education including teachers. Teacher professionalism becomes a question in relation to the implementation of the 2013 revised 2018 curriculum. For Vocational High School teachers, for the content of vocational specialization in business and management, especially in accounting and financial institutions, there has been a change in the expertise competency section, one of the most stealing changes attention is the emergence of subjects